MORPHOLOGICAL, HISTOCHEMICAL, AND STATISTICAL EVALUATION OF ISCHEMIC CHANGES IN GASTRIC TISSUE IN METABOLIC SYNDROME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Metabolic syndrome (MS) is a multifactorial pathological condition characterized by disturbances in carbohydrate and lipid metabolism, arterial hypertension, central obesity, and insulin resistance. It is increasingly recognized as a systemic disorder affecting not only the cardiovascular and endocrine systems but also the digestive organs, including the stomach. Recent studies have drawn attention to the adverse impact of MS on gastric tissue morphology and function. One of the critical pathophysiological consequences of MS is microcirculatory dysfunction, leading to tissue hypoxia and ischemic alterations. Gastric tissue is particularly sensitive to ischemia, and compromised blood supply can result in trophic disturbances, atrophy of the mucosa, chronic inflammation, and, in some cases, progression to preneoplastic changes. In this context, morphological and histochemical analyses play a vital role in identifying and characterizing ischemic damage at the tissue level. Literature indicates that ischemic injury in various tissues is accompanied by endothelial damage, vascular degradation, epithelial apoptosis, and fibrotic remodeling. Therefore, evaluating the ischemic changes in gastric tissue of patients with metabolic syndrome using histomorphological and histochemical methods, supported by statistical analysis, holds significant scientific and practical relevance. This study aims to analyze the ischemic changes in the gastric tissues of individuals with metabolic syndrome through morphological and histochemical techniques and to assess the extent and distribution of these changes using statistical methods.